Analisis Strategi Manajemen Berbasis Sekolah dalam Meningkatkan Mutu Pendidikan di Era Digital pada SMP AN Namiroh Pekanbaru - Susiwati (Kilau Publishing, 2026)
This research is motivated by the suboptimal implementation of school-based management in improving the quality of education in the digital era, particularly in the utilization of technology and the involvement of the school community. This study aims to analyze the strategy of school-based management in improving the quality of education at SMP AN Namiroh Pekanbaru. The research method uses a qualitative approach with a descriptive design. The research subjects consisted of three people, the principal, teachers, and education staff. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis techniques used data reduction, data presentation, and drawing conclusions. The results show that the school-based management strategy implemented includes digital-based planning, technology-based learning implementation, visionary leadership of the principal, and active participation of the school community. The implementation of this strategy has a positive impact on improving the quality of education, especially in student engagement and learning effectiveness. Obstacles found include limited digital competence of teachers and suboptimal integration of technology systems.